The Effect of Government Debt on Private Investment in Advanced Economies: Does Institutional Quality Matter? - Van Bon Nguyen (Scientific Annals of Economics and Business, 2022)
Unlike developing economies, advanced economies easily borrow debt to finance budget deficits. Government debt is one of the active measures of fiscal policy in these economies to run the economy and overcome its cyclicality. Most related studies note that government debt reduces private investment. Does it hold for advanced economies? Does institutional quality significantly affect the government debt – private investment relationship in these economies? For the answer, the study applies the PMG estimator (PMG) and the two-step difference GMM Arellano & Bond estimator (D-GMM) to investigate the impacts of government debt, institutional quality, and their interaction on private investment in 36 advanced economies from 2002 through 2019. The estimated results report that government debt crowds out private investment, while institutional quality enhances it. However, their interaction crowds out it. It seems counter-intuitive. Besides, economic growth and trade openness increase private investment while inflation decreases it. These results indicate the crucial implications for central governments in advanced countries in using and managing government debt.